(untitled) (El-Wahat Journal for Research and Studies, 2025)
This Study Aims To Trace The Woman’s Manifestations In The Novel “Loss In The Sea” By Hafnawizagiz, And To Reveal The Aesthetic Ways In Which The Writer Portrays Her. The Study Will Be Limited To Studying The Two Images: The Mysterious And The Friendly Women, As They Are Two Main Images Related To The Character Of "Sinan" In Which The Events Of The Novel Took Place. Reading The Novel Reveals The Image Of The Mysterious Woman, The Friendly Woman, The Enigmatic Woman, The Domineering Wife, The Old Woman, The Mother, And The Sister. However, One Of The Most Important Conclusions Of The Reading Process Is That The Novel Showed That Women And Drugs Were A Cause Of Loss And Destruction. Keywords: Women; Aesthetic; Reading; Ambiguity; Hafnawyzagiz.